Impact of pain and functional impairment in US adults with haemophilia: Patient‐reported outcomes and musculoskeletal evaluation in the pain, functional impairment and quality of life (P‐FiQ) study. Issue 2 (8th December 2017) - Kempton, C. L.; Recht, M.; Neff, A.; Wang, M.; Buckner, T. W.; Soni, A.; Quon, D.; Witkop, M.; Boggio, L.; Gut, R. Z.; Cooper, D. L.
Abstract : Introduction: Standardized and disease‐specific patient‐reported outcome (PRO) instruments assessing pain, functional impairment and health‐related quality of life (HRQoL) in people with haemophilia (PWH) have been used in studies, but infrequently in comprehensive care settings for individual assessment or treatment planning. Aim: To assess the impact of pain and functional impairment on HRQoL in PWH. Methods: P‐FiQ enrolled 381 adult PWH with a history of joint pain/bleeding and included 5 PROs and a clinical joint evaluation (Hemophilia Joint Health Score v2.1 [HJHS]). Results: Median age was 34 years; 49.9% reported a history of joint procedure or surgery. On EQ‐5D‐5L, most reported problems with mobility (61.4%), usual activities (53.2%) and pain/discomfort (76.1%). On Brief Pain Inventory v2 Short Form, median worst pain (range 0‐10) was 6, least pain 1, average pain 3 and current pain 2. Ankles were most frequently reported as the most painful joints (37.4%), followed by knees (23.7%) and elbows (18.9%). On International Physical Activity Questionnaire, 51% reported no activity in the prior week. On SF‐36v2 health survey, median subscores were worse for 4 physical health domains vs 4 mental health domains. Among Hemophilia Activities List domains (range 0 [worst]‐100 [best]), functions of the legs (median, 66.7) and lying/sitting/kneeling/standing (median, 67.5) were most impacted and self‐care least impacted (median, 100.0). On HJHS, ankle scores (median, 6.0; range, 0‐40) were worse than elbow/knee scores (median, 4.0/4.0). Results were consistent across PROs/HJHS. Conclusion: Data demonstrate challenges of predominantly ankle/knee pain and lower extremity functional impairment in US adult PWH, affecting HRQoL across PROs/HJHS.